1987
DOI: 10.1172/jci112885
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 inhibits effector T cell induction and tissue damage in experimental murine interstitial nephritis.

Abstract: Immunosuppressive effects of E-series prostaglandins have been demonstrated in many in vitro assays of immune responsiveness as well as in autoimmune diseases. To explore the mechanisms underlying prostaglandin El (PGE1)-associated immunosuppression in autoimmunity, we treated SJL mice immunized to produce immune-mediated interstitial nephritis with PGE1, PGFu, or vehicle alone. Mice receiving PGE1 treatment do not develop interstitial nephritis, nor do they display delayed-type hypersensitivity (DTH) to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…CEI has been shown to enhance the cyclooxygenase pathway of arachidonic acid metabolism in blood vessels and isolated glomeruli (38,(49)(50)(51). Products ofthe cyclooxygenase pathway, in turn, directly or indirectly attenuate cell proliferation (38,(52)(53)(54)(55)(56)(57)(58). In our recent preliminary study a strong correlation was found between glomerular hypertrophy and sclerosis at the single nephron level in a model of subtotal nephrectomy (59).…”
Section: Resultsmentioning
confidence: 99%
“…CEI has been shown to enhance the cyclooxygenase pathway of arachidonic acid metabolism in blood vessels and isolated glomeruli (38,(49)(50)(51). Products ofthe cyclooxygenase pathway, in turn, directly or indirectly attenuate cell proliferation (38,(52)(53)(54)(55)(56)(57)(58). In our recent preliminary study a strong correlation was found between glomerular hypertrophy and sclerosis at the single nephron level in a model of subtotal nephrectomy (59).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate further the mechanism by which TEI-6122 exhibits an extremely high potency in inhibiting MCP-l-induced THP-1 cell chemotaxis, it may be useful to examine the affinity of TEI-6122 for the EP receptor subtypes in detail. It has been shown that PGs of the E series have a number of anit-inflammatory effects (Zurier & Quagliata, 1971;Fantone et al, 1983;Kelly et al, 1987), although the mechanisms of these anti-inflammatory effects are not clear. It has been recently reported that the administration of PGE1 or a synthetic PGE2 derivative decreases the content of macrophages in the kidney in either a rat renal allograft model or a rat glomerulonephritis model (Cattell et al, 1990;Schreiner et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper, we focused on prostaglandins (PGs) as possible inhibitors of MCP-1-induced chemotaxis, since there have been reports that PGs of the E series exhibit anti-inflammatory properties (Zurier & Quagliata, 1971;Fantone et al, 1983;Kelly et al, 1987), and also that intracellular adenosine 3': 5'-cycic monophosphate (cyclic AMP) accumula-'Author for correspondence. tion can result in inhibition of neutrophil chemotaxis (Harvath et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Lymphokine alterations could play a role in pathogenesis. In an ex perimental model of murine interstitial nephritis, Kelly et al [10] showed that prostaglandin El (PgE-l) administration suppressed the development of interstitial nephritis by inhi biting effector T-cell induction in immunized mice. The dosage of PgE-l utilized was similar to that used previously by the authors to induce release of suppressor lymphokines by T lymphocytes.…”
Section: Pathogenesismentioning
confidence: 99%